Haemophilus influenzae type b carriage and novel bacterial population structure among children in urban Kathmandu, Nepal. - Williams, E; Lewis, J; John, T; Hoe, J; Yu, L; Dongol, S; Kelly, D; Griffiths, D; Shah, A; Limbu, B; Pradhan, R; Mawas, F; et al. (2011)
Haemophilus influenzae type b (Hib) is a major cause of invasive bacterial infection in children that can be prevented by a vaccine, but there is still uncertainty about its relative importance in Asia. This study investigated the age-specific prevalence of Hib carriage and its molecular epidemiology in carriage and disease in Nepal. Oropharyngeal swabs were collected from children in Kathmandu, Nepal, from 3 different settings: a hospital outpatient department (OPD), schools, and children's homes. Hib was isolated using Hib antiserum agar plates, and serotyping was performed with latex agglutination. Hib isolates from children with invasive disease were obtained during active microbiological surveillance at Patan Hospital, Kathmandu, Nepal. Genotyping of disease and carriage isolates was undertaken using multilocus sequence typing (MLST). Swabs were taken from 2,195 children, including 1,311 children at an OPD, 647 children attending schools, and 237 children in homes. Overall, Hib was identified in 5.0% (110/2,195; 95% confidence interval [95% CI], 3.9% to 6.4%). MLST was performed on 108 Hib isolates from children carrying Hib isolates and 15 isolates from children with invasive disease. Thirty-one sequence types (STs) were identified, and 20 of these were novel STs. The most common ST isolates were sequence type 6 (ST6) and the novel ST722. There was marked heterogeneity among the STs from children with disease and children carrying Hib. STs identified from invasive infections were those commonly identified in carriage. This study provides evidence of Hib carriage among children in urban Nepal with genetically diverse strains prior to introduction of universal vaccination. The Hib carriage rate in Nepal was similar to the rates observed in other populations with documented high disease rates prior to vaccination, supporting implementation of Hib vaccine in Nepal in 2009.